KAJIAN EDUKASI RAMAH LINGKUNGAN DAN KARAKTERISTIK KONSUMEN SERTA PENGARUHNYA TERHADAP SIKAP DAN PERILAKU RAMAH LINGKUNGAN - Budi Kusumo, Rani Andriani; Charina, Anne; Sukayat, Yayat; Mukti, Gema Wibawa (Jurnal Ilmu Keluarga dan Konsumen, 2017)
The quality decreasing of the environment could be caused by household consumption behavior. Consumer's positive attitude toward environmental issues can be encouraged through socialization about eco-friendly lifestyles. Kelompok Tani Cipta Mandiri is one of the organic vegetable producers that used eco-friendly issues marketing. This study were aimed to analyze eco-friendly education which was conducted by Cipta Mandiri farmer group; consumer attitudes about environmental issues; and the influence of eco-friendly education and demographic characteristics toward consumer eco-friendly attitude and behavior. Respondents in this study were 60 consumers who bought through the 'Small Market'. Descriptive and path analysis were used to accomplish the objectives of this study. The results showed that eco-friendly education which is conducted by Cipta Mandiri farmers group encourages consumers' positive behaviour about environment friendly issues. Most of the consumers understood the purpose and benefits of educational activities, feel attracted to these activities, and be willing to behave environment friendly. The income had significantly influence on the consumer's attitude, especially affective and conative dimensions. Meanwhile, consumer's attitude had a positive impact on eco-friendly behavior. Therefore, government or other institutions can encourage producers to do social business activities to increase consumer awareness of environment friendly behavior.